Implications of the Minamata Convention on Mercury on Oral Health in Kenya - Osiro, Olivia; Kisumbi, Bernina; Kariuki, David; Gathece, Loice (University of Nairobi, 2020)
Despite the high prevalence of tooth decay, oral health is poorly funded and receives only 0.0016 per cent of the national budget for health, limited to 8 per cent of the total Government expenditure (Kaimenyi, 2004). This provision is grossly inadequate. Therefore, access to restorative dental care remains limited for the majority and often, removal of offending teeth is a cheaper alternative. Tooth loss affects mastication and speech and is associated with reduced quality of life (Petersen, 2004; Petersen, 2007). For those who can access treatment in the form of fillings, dental amalgam remains the most readily available and preferred filling material in low- and middle-income countries, including Kenya, as it is inexpensive, easy to use, and strong enough to withstand chewing forces (Petersen et al., 2009). Therefore, the phase-down of dental amalgam will have implications on oral health status in Kenya through the unavailability of affordable dental treatment.
Keywords: Kenya; Oral health